2019
DOI: 10.1063/1.5097829
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine wake intermittency dependence on turbulence intensity and pitch motion

Abstract: Turbulence intermittency characteristics of the flow behind pitching and fixed wind turbines are assessed via hot-wire anemometry in a wind tunnel experiment. The pitching wind turbine model is free to oscillate in the streamwise direction to simulate pitch motion. Two inflow conditions are considered: 15% and 1.8% turbulent intensities. Empirical mode decomposition and Hilbert Huang transform are employed and validated by comparing the Hilbert energy spectrum with the Fourier energy spectrum. The extended sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Across techniques, prior descriptions of eddy viscosity have relied on a global approach to represent turbulence in both the background and wake flows conflating boundary layer phenomena occurring at large scales with localized wake behavior. Additionally, Rockel et al (2014Rockel et al ( , 2016 and Kadum et al (2019Kadum et al ( , 2021 found the eddy viscosity and intermittency of a floating offshore turbine was affected by wave-induced pitch motion which is not present in current models. Finally, the streamwise behavior of eddy viscosity has yet to be quantified in a parametric study spanning multiple inflow conditions, turbine sizes, and misalignment angles.…”
Section: Introductionmentioning
confidence: 89%
“…Across techniques, prior descriptions of eddy viscosity have relied on a global approach to represent turbulence in both the background and wake flows conflating boundary layer phenomena occurring at large scales with localized wake behavior. Additionally, Rockel et al (2014Rockel et al ( , 2016 and Kadum et al (2019Kadum et al ( , 2021 found the eddy viscosity and intermittency of a floating offshore turbine was affected by wave-induced pitch motion which is not present in current models. Finally, the streamwise behavior of eddy viscosity has yet to be quantified in a parametric study spanning multiple inflow conditions, turbine sizes, and misalignment angles.…”
Section: Introductionmentioning
confidence: 89%
“…The floating offshore wind turbines represent a highly promising form of renewable energy technology with the potential to provide clean and sustainable electricity worldwide, which can reduce dependence on traditional fossil fuels. However, compared with fixed offshore wind turbines, floating offshore wind turbines (FOWTs) are influenced by the motion of the floating platform, leading to variations in aerodynamic loads and power output of the turbines [2][3][4][5]. Moreover, the wind turbines are subjected to vibrations and stress induced by the platform's motion, which may result in structural fatigue and reduced lifespan of the turbines.…”
Section: Introductionmentioning
confidence: 99%
“…For a floating wind turbine (FWT), an interaction between the floater dynamics, the atmosphere, and the wake is expected and consequences are anticipated on the power curve, the wake meandering, the wake interactions and, finally, on the fatigue of downstream turbines that could potentially challenge current In the last five years, only a limited number of numerical and experimental studies have been analysing the effect of FWT motions on the far wake with a main interest on pitch and roll motions. Using a rotating wind turbine model at a 1/400 scale, [1,2,3] focused their laboratory research on the analysis of the modifications of the wake due to pitch and roll motion in a frequency range of 1.2 Hz -1.8 Hz with an amplitude of 15 • . In their wind tunnel experiment, [5], found that the pitch and roll motion in the range 5 • to 20 • have a visible signature in the wake of a rotative wind turbine model that vanishes after 7 diameters downstream.…”
Section: Introductionmentioning
confidence: 99%